Analisis Standar Isi Bahasa Inggris SMP dan SMA - Mutiara O Panjaitan (Jurnal Pendidikan dan Kebudayaan, 2013)
The purpose of this paper is to analyze: 1) The efficiency of formulation of competenceÂ standards and basic competence; 2) Readability of competence standards and basic competence;Â 3) Clarity of Scope of material; 4) The degree of difficulty of competence standards and basicÂ competence, 5) The use of linguistic terms on competence standards and basic competence,Â and 6) Gradation of each genre. The analysis was done with reference to the theory of languageÂ presented in this paper which is also used as the basis for the development of content standards.Â The results showed that: First, separation of receptive and productive competence caused a lotÂ of repetition in formulating competence standards and basic competence; Second, competenceÂ standards and basic competence grouping according to language skills (listening, speaking,Â reading, writing) tend to be understood by teachers as a separate four language skills; Third,Â linguistic competence is mentioned with the words â€œaccuracy, acceptance and fluencyâ€ withoutÂ specification that need to be covered so that raises multiple interpretations; Fourth, The difficultyÂ level of competence is above the ability of average junior high school students; Fifth, theÂ formulation of competence standards and basic competence use so many linguistic terms thattend to be theoretical that teachers difficult to interpret it; Sixth, there is no radation of eachgenre.Â ABSTRAKÂ Tujuan analisis ini yaitu untuk menganalisis: 1) Efisiensi rumusan standar kompetensiÂ dan kompetensi dasar; 2) Keterbacaan standar kompetensi dan kompetensi dasar; 3) KejelasanÂ ruang lingkup materi; 4) Tingkat kesulitan standar kompetensi dan kompetensi dasar; 5)Â Penggunaan istilah linguistik pada rumusan kompetensi; dan 6) Gradasi masing-masing genre.Â Analisis dilakukan dengan mengacu pada teori bahasa yang dipaparkan yang digunakan sebagai landasan pengembangan standar isi tersebut. Hasil analisis sebagai berikut: Pertama, pemisahanÂ tindakan reseptif dan produktif menyebabkan banyak pengulangan dalam merumuskan standarÂ kompetensi dan kompetensi dasar; Kedua, pengelompokan standar kompetensi dan kompetensiÂ dasar menurut keterampilan berbahasa (mendengarkan, berbicara, membaca, dan menulis) cenderung dipahami guru sebagai empat keterampilan berbahasa yang terpisah; Ketiga,Â kompetensi linguistik disebutkan dengan kata-kata â€œkeakuratan, keberterimaan, dan kelancaranâ€Â tanpa spesifikasi lingkup materi yang perlu dicakup sehingga menimbulkan multitafsir; Keempat,Â tingkat kesulitan kompetensi di atas kemampuan rata-rata peserta didik Sekolah Menengah Pertama; Kelima, rumusan standar kompetensi dan kompetensi dasar banyak menggunakanÂ istilah linguistik cenderung teoretis sehingga guru sulit menjabarkannya; Keenam, tidak terlihatÂ gradasi kesulitan masing-masing genre.Â